2017
DOI: 10.1016/j.neurobiolaging.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Reduced dopamine receptors and transporters but not synthesis capacity in normal aging adults: a meta-analysis

Abstract: Many theories of cognitive aging are based on evidence that dopamine (DA) declines with age. Here we performed a systematic meta-analysis of cross-sectional PET and SPECT studies on the average effects of age on distinct DA targets (receptors, transporters, or relevant enzymes) in healthy adults (N=95 studies including 2,611 subjects). Results revealed significant moderate to large, negative effects of age on DA transporters and receptors. Age had a significantly larger effect on D1- than D2-like receptors. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
195
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 214 publications
(215 citation statements)
references
References 75 publications
7
195
4
Order By: Relevance
“…While we estimated declines of 6–16% in lateral temporal and many frontal cortical regions, we estimated striatal D2‐like declines between 1.5 and 5% per decade. The estimates reported here are somewhat lower than those seen in a recent meta‐analysis (Karrer et al, ), and could be due to our use of partial volume correction, an extremely healthy sample, or both. For instance, prior work from our lab on a subset of data from Study 1 noted that age‐related changes in the uncorrected data more closely resemble those seen in the meta‐analysis (Smith et al, ), while another study showed that compared to more sedentary adults, age‐related change in striatal D2 BP ND is less steep in physically active adults (Dang et al, ).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…While we estimated declines of 6–16% in lateral temporal and many frontal cortical regions, we estimated striatal D2‐like declines between 1.5 and 5% per decade. The estimates reported here are somewhat lower than those seen in a recent meta‐analysis (Karrer et al, ), and could be due to our use of partial volume correction, an extremely healthy sample, or both. For instance, prior work from our lab on a subset of data from Study 1 noted that age‐related changes in the uncorrected data more closely resemble those seen in the meta‐analysis (Smith et al, ), while another study showed that compared to more sedentary adults, age‐related change in striatal D2 BP ND is less steep in physically active adults (Dang et al, ).…”
Section: Discussioncontrasting
confidence: 90%
“…Specifically, studies of D2-like receptor BP ND report wide-ranging age-related effects, ranging from slightly negative (Kim et al, 2011) to strongly negative (Bäckman et al, 2000;Mukherjee et al, 2002). A recent meta-analysis showed strongly negative linear effects of adult age on D2-like receptors in both frontal (r = −0.66) and striatal (r = −0.54) regions (Karrer, Josef, Mata, Morris, & Samanez-Larkin, 2017). In exploratory analyses, this meta-analysis also showed that linear and quadratic effects of age fit the data equally well.…”
mentioning
confidence: 99%
“…The age-related decrease in MOR availability observed in thalamus, amygdala and nucleus accumbens is consistent with the general pattern of ageing-related brain atrophy, emerging as reduced cortical thickness and reduced grey and white matter volume 39 . Many other receptor systems, including serotonergic and dopaminergic systems, undergo receptor loss with advancing age 40,41 . The decrease in MOR availability likely reflects similar receptor loss.…”
Section: Effects Of Age On Endogenous Opioid Systemmentioning
confidence: 99%
“…D 2 ‐like binding potential in the VTA also shows little age‐related change, with some reports finding evidence of increased binding potential in this region (Matuskey et al, ; Nakajima et al, ). Reduced striatal binding potential with age may also be offset by dopamine synthesis capacity and age‐related decline in dopamine transporters (Karrer et al, ), as the former shows relative stability across adulthood and the latter should result in lower dopamine reuptake in the synaptic cleft among older adults. Complementary research using diffusion tensor imaging (DTI) has shown that structural connections between the ventral striatum and medial prefrontal cortex (mPFC) are negatively associated with age, but connections between the VTA and ventral striatum are positively associated with age (Samanez‐Larkin et al, ).…”
Section: Age‐related Change To Neural Substrates Of Decision‐makingmentioning
confidence: 99%